2012
DOI: 10.1002/jor.22126
|View full text |Cite
|
Sign up to set email alerts
|

In‐vivo patellar tendon kinematics during weight‐bearing deep knee flexion

Abstract: This study quantified in-vivo 3D patellar tendon kinematics during weight-bearing deep knee bend beyond 1508. Each knee was MRI scanned to create 3D bony models of the patella, tibia, femur, and the attachment sites of the patellar tendon on the distal patella and the tibial tubercle. Each attachment site was divided into lateral, central, and medial thirds. The subjects were then imaged using a dual fluoroscopic image system while performing a deep knee bend. The knee positions were determined using the bony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In this study, we have investigated in vivo length changes between femoral-patellar graft insertion points using a custom-made algorithm for path generation. Similar methods were described previously for estimating 3D length changes of ligaments in the knee [9,27,28] and for other anatomy [5,11,14,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have investigated in vivo length changes between femoral-patellar graft insertion points using a custom-made algorithm for path generation. Similar methods were described previously for estimating 3D length changes of ligaments in the knee [9,27,28] and for other anatomy [5,11,14,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that in general, the patella shifted laterally and tilted laterally along the flexion path of the knee [10]. After 60 deg of flexion, the patellar shift and tilt were almost constant while the patellar tilted medially at 150 deg.…”
Section: Discussionmentioning
confidence: 95%
“…3). If the line intersected with the tibial bony surface, a line tangential to the intersected tibial bony surface was drawn from each attachment site to represent the effect of the tendon wrapping on the bone [10]. The orientation of the quadriceps was assumed to be parallel to the femoral shaft since the IVIRI could not capture the entire quadriceps from their origins to insertions.…”
Section: Fig 1 a Virtual Dual F Luoroscopic Image Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pathomechanics of PFP are not fully understood. Recent studies have evaluated in vivo patellofemoral kinematics statically (Noehren et al, 2011; Salsich and Perman, 2012) or during activities like deep knee flexion (Behnam et al, 2011; Kobayashi et al, 2012; Powers et al, 2003). These studies have computed patellofemoral kinematics using an anatomical coordinate system (ACS) that was determined using manual point selection methods (Fellows et al, 2005) or by fitting a bounding box (Li et al, 2007; Nha et al, 2008).…”
Section: Introductionmentioning
confidence: 99%